Pengaruh Kombinasi Pupuk Kompos dan NPK Terhadap Pertumbuhan, Jumlah Klorofil A dan Kadar Air Gracilaria verrucosa [Effect Of Compost and NPK Fertilizer Combinations On Growth, Chlorophyll A and Water Content Of Gracilaria verrucose] - Mochammad Amin Alamsjah; Iva Nur Silviana; Kadek Rachmawati (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
AbstractIn general, Gracilaria culture still using organic and inorganic fertilizer single. Organic or inorganic fertilizer applied is felt have not yet enough to support the growth of Gracilaria. The aim of this experiment was to know the best compost and NPK combinations which could influence on growth, chlorophyll a and water content of G.verrucosa. Treatment applied was compost and NPK combinations with different doses, that is A treatment (0 gr/l :  2 gr/l), B treatment (0,5 gr/l : 1,5 gr/l), C treatment (1 gr/l : 1gr/l), D treatment (1,5 gr/l : 0,5 gr/l), E treatment (2 gr/l : 0 gr/l) and F treatment (without fertilizer), each treatment was replicated 4 times. Main parameter observed was daily growth rate (%/day), relative length growth (%), chlorophyll a (í¬g/ml) and water content (%) of G.verrucosa. oSupported parameter observed was pH, temperature ( C) and salinity ("°). Data analysis using Analysis of Variance (ANOVA) and Duncan Multiple Range Test. Result of  the experiment indicates that compost and NPK combinations with different doses was significantly influence to growth, chlorophyll a and water content of G. verrucosa. The highest mean of daily weight growth rates was C treatment (1 gr/l : 1gr/l) which was equal to 2,56%/day and the lowest mean was  F treatment (without fertilizer) which was equal to 1,12%/day. The highest mean of relative length growth was C treatment (1 gr/l : 1gr/l) which was equal to 2,21% and the lowest mean was F treatment (without fertilizer) which was equal to 0,60%. The highest mean of chlorophyll a by the end of the experiment was C treatment (1 gr/l : 1gr/l) which was equal to 0,001948 í¬g/ml and the lowest mean was F treatment (without fertilizer) which was equal to 0,001440 í¬g/ml. The lowest mean of water content by the end of the experiment was C treatment (1 gr/l : 1gr/l) which was equal to 28,48 % and the highest mean was F treatment (without fertilizer) which was equal to 30,39%.